Polarização, energia e momento de ondas eletromagnéticas e fótons em diferentes referenciais inerciais - Ricardo Simao Pereira Lopes (2017)
In this work, we analyze the the classical electromagnetic waves and photon behavior under Lorentz transformations. We show that a proportionality ratio between energy and angular frequency is compatible with not only the quantum case (photons) but also with the classical phenomena. Likewise we treat the transformation of the momentum and wave vector showing an equalproportionalityratio. We analyze also the polarization state under this transformations and we verify that this state is invariant under the change of reference frame in classical and quantum cases. For the photon treatment we use the photon wave function introduced by Bialinicki-Birula and Sipe, but unlike the references, we will give up the explicitly covariant approach taken by then for more intuitive approach. We hope this work help the physical comprehension of the phenomena analyzed, and we also hope that this work can be useful in relativistic quantum information theory.